Merging C–C σ-bond activation of cyclobutanones with CO2 fixation via Ni-catalysis. Issue 25 (9th March 2022) - Lombardi, Lorenzo; Cerveri, Alessandro; Ceccon, Leonardo; Pedrazzani, Riccardo; Monari, Magda; Bertuzzi, Giulio; Bandini, Marco
Abstract : A carboxylative Ni-catalyzed tandem C–C σ-bond activation of cyclobutanones followed by CO2 -electrophilic trapping is documented as a direct route to synthetically valuable 3-indanone-1-acetic acids. Abstract : A carboxylative Ni-catalyzed tandem C–C σ-bond activation of cyclobutanones followed by CO2 -electrophilic trapping is documented as a direct route to synthetically valuable 3-indanone-1-acetic acids. The protocol shows an adequate functional group tolerance and useful chemical outcomes (yield up to 76%) when AlCl3 is adopted as an additive. Manipulations of the targeted cyclic scaffolds and a mechanistic proposal based on experimental evidence complete the investigation.